2023
DOI: 10.1037/fam0001106
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between parental reflective functioning and maternal mind-mindedness.

Abstract: Little work has examined longitudinal associations between parental reflective functioning (PRF) and mind-mindedness (MM), limiting the understanding of separate or bidirectional trajectories of these related but distinct forms of mentalization. We examined cross-lagged associations between PRF, assessed via interview, and MM, coded from play interactions, over 12 months among 90 parents (86% female; 57% White, 43% Black) of infants (Mage = 10.56 months, SD = 8.20) who were participating in The Michigan Model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The sociodemographic factors examined across studies typically include income level, education level, maternal age, and single parenthood. Multiple studies have documented significant associations between level of parental education and PRF (Alismail et al, 2022;Arkle et al, 2023;Benbassat & Priel, 2012;Brophy-Herb et al, 2023;Halfon & Besiroglu, 2020;Huber et al, 2015;Lowell et al, 2022;Newman-Morris et al, 2020;Sleed et al, 2018;Stover & Kiselica, 2014). Similarly, a significant association between maternal income level and PRF has been reported in at least four studies (Arkle et al, 2023;Brophy-Herb et al, 2023;Sleed et al, 2018;Yatziv et al, 2020).…”
Section: Sociodemographic Riskmentioning
confidence: 89%
See 1 more Smart Citation
“…The sociodemographic factors examined across studies typically include income level, education level, maternal age, and single parenthood. Multiple studies have documented significant associations between level of parental education and PRF (Alismail et al, 2022;Arkle et al, 2023;Benbassat & Priel, 2012;Brophy-Herb et al, 2023;Halfon & Besiroglu, 2020;Huber et al, 2015;Lowell et al, 2022;Newman-Morris et al, 2020;Sleed et al, 2018;Stover & Kiselica, 2014). Similarly, a significant association between maternal income level and PRF has been reported in at least four studies (Arkle et al, 2023;Brophy-Herb et al, 2023;Sleed et al, 2018;Yatziv et al, 2020).…”
Section: Sociodemographic Riskmentioning
confidence: 89%
“…Multiple studies have documented significant associations between level of parental education and PRF (Alismail et al, 2022;Arkle et al, 2023;Benbassat & Priel, 2012;Brophy-Herb et al, 2023;Halfon & Besiroglu, 2020;Huber et al, 2015;Lowell et al, 2022;Newman-Morris et al, 2020;Sleed et al, 2018;Stover & Kiselica, 2014). Similarly, a significant association between maternal income level and PRF has been reported in at least four studies (Arkle et al, 2023;Brophy-Herb et al, 2023;Sleed et al, 2018;Yatziv et al, 2020). In their study of fathers, Buttitta et al (2019) found that economic disadvantage impinged on parental behavior only if the father also had low levels of CF-RF.…”
Section: Sociodemographic Riskmentioning
confidence: 90%